Not in My Community: Social Pressure and the Geography of Dismissals - Andrea Bassanini; Giorgio Brunello; Eve Caroli (Institute for the Study of Labor (IZA), 2015)
We investigate the role of local social pressure in shaping the geographical pattern of firms' firing decisions. Using French linked employer-employee data, we show that social pressure exerted by the local communities where firms' headquarters are located induces CEOs to refrain from dismissing at short distance from their headquarters. More specifically, we find that, within firms, secondary establishments located further away from headquarters have higher dismissal rates than those located closer, taking into account the possible endogeneity of plant location. We also find that the positive effect of distance on dismissals increases with the visibility of the firm in the local community of its headquarters. These effects are stronger the greater the degree of selfishness of the community in which the headquarters are located. This suggests that local social pressure at headquarters is a key determinant of the positive relationship between distance to headquarters and dismissals. We show that our results cannot be entirely accounted for by alternative explanations of the distance-dismissal relationship that are put forward in the literature e.g. monitoring costs or asymmetric information.
Keywords: J23; J63; M51; R12; 330; social pressure; layoffs; adjustment costs; selfishness; firm visibility; distance to headquarters